Improvement of Soft Bangkok Clay using Kaolin-Quick Lime Geopolymer - Suman Manandhar; Panich Voottipruex; Siripat Maneekaew; Chairat Teerawattnasuk; Ittipon Meepon (International Association of Lowland Technology, 2020)
The engineering properties of C-QG geopolymer were evaluated to ascertain the viability of using this material as an embankment structure fill material and also the efficacy of geopolymer stabilization in improving mechanical behavior of soft clay. Results from strength assessments with the usage of UCS and indirect tensile strength were used to establish the performance of the C-QG geopolymer. Quicklime mixed with 6 molar NaOH gave the maximum unconfined compressive strength. qu of the samples increases significantly to 127% as the temperature increase from 28 °C to 70 °C indicating that the optimum curing temperature was 70 °C. Elastic modulus of samples increases with curing temperature increase. The mixing ratio of C:QG 60:40 exhibited highest elastic modulus. E50 increases with increasing in geopolymer content and approximately equal to 869.82qu. This secant modulus can be used for pavement design in Thailand. The highest indirect strength at all curing temperatures was obtained samples with mixing ratio of C:QG 80:20. The curing temperature increased from 28 °C to 70 °C, the indirect tensile strength increased by 50 percent indicating that the optimal curing temperature is 70 °C. The strength development from the UCS tests demonstrates the binding properties of the QG geopolymers. At curing temperature of 70 °C, the sample exhibit more particle arrangement than the sample curing under 70 °C . It can be anticipated that the curing temperature of 70 degrees is suitable for polymerization reaction.